High-throughput characterization of early oxidation across AlxFeyNi1−x−y composition space. (February 2015) - Payne, Matthew A.; Miller, James B.; Gellman, Andrew J.
Highlights: Thin-film combinatorial libraries can contain every AlFeNi alloy composition. We have studied oxidation of full-range AlFeNi libraries in dry air at 427 °C. High-throughput methods were developed to characterize oxidation behaviour. Four phenomenologically distinct regions are identified across AlFeNi space. The continuous boundary of internal/external oxidation transition is identified. Abstract: Improving our fundamental understanding of the oxidation of multicomponent alumina-forming alloys is crucial to their ongoing development. In this work, high-throughput methods were developed to study oxidation of Al x Fe y Ni1− x − y alloys in dry air at 427 °C using composition spread alloy films as combinatorial libraries ( x  = 0 → 1, y  = 0 → [1− x ]). The results divide the Al x Fe y Ni1− x−y composition space into four regions of phenomenologically distinct oxidation behaviour. The boundary defining the critical Al concentration, N Al ∗ ( x, y ), for establishment of a passivating Al2 O3 scale was determined across the entire continuous Al x Fe y Ni1− x − y composition space.